Design and Development of an Electric Gokart Prototype ‘E-Andalasian’ for Sustainable Campus Transportation - Saputra, Dendi Adi; Dahlan, Hendery; Satria, Eka; Susanti, Lusi; Khairul, Fajri; Nabil, M. Naufalunn; Gusnanda, Raihan; Joice Natalie, Ezra; Fadhillah, M. Ahlan (Andalasian International Journal of Applied Science, Engineering and Technology, 2025)
This research focuses on the design, development, and optimization of the electric go-kart "E-Andalasian" as an environmentally friendly campus transportation solution. Structural analysis was performed using Finite Element Analysis (FEA) to evaluate stress distribution and deformation under static and dynamic loads. The study also optimizes the BLDC motor, 72V 40Ah lithium battery, and controller to achieve efficient and reliable performance. Results indicate critical stress points at wheel joints, with recommendations for aluminum alloy use to enhance weight efficiency. Experimental testing showed that the motor achieved a maximum torque of 44.52 N.m and 6447 RPM, while the battery supports a range of 40 km with a charging time of 2 hours 9 minutes. Although the maximum speed reached 59 km/h, additional optimization is required to meet the original design target. The findings provide a prototype foundation for future improvements and contribute to green campus mobility.